2006
DOI: 10.1002/jpln.200520557
|View full text |Cite
|
Sign up to set email alerts
|

Salt‐resistant and salt‐sensitive wheat genotypes show similar biochemical reaction at protein level in the first phase of salt stress

Abstract: Salinity has a two-phase effect on plant growth, an osmotic effect due to salts in the outside solution and ion toxicity in a second phase due to salt build-up in transpiring leaves. To elucidate salt-resistance mechanisms in the first phase of salt stress, we studied the biochemical reaction of salt-resistant and salt-sensitive wheat (Triticum aestivum L.) genotypes at protein level after 10 d exposure to 125 mM-NaCl salinity (first phase of salt stress) and the variation of salt resistance among the genotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
27
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 27 publications
6
27
0
Order By: Relevance
“…Moreover, a dramatic change in protein pattern under low salt concentration does not necessarily affect biomass production and ion concentration. Similar conclusions were drawn by Saqib et al (2006) for salt-resistant and salt-sensitive genotypes of wheat. On the other hand, only a limited change in the proteomes of Oryza sativa and Nicotiana tobaccum were found under salt stress (Abbasi and Komatsu, 2004;Razavizadeh et al, 2009).…”
Section: Introductionsupporting
confidence: 83%
See 1 more Smart Citation
“…Moreover, a dramatic change in protein pattern under low salt concentration does not necessarily affect biomass production and ion concentration. Similar conclusions were drawn by Saqib et al (2006) for salt-resistant and salt-sensitive genotypes of wheat. On the other hand, only a limited change in the proteomes of Oryza sativa and Nicotiana tobaccum were found under salt stress (Abbasi and Komatsu, 2004;Razavizadeh et al, 2009).…”
Section: Introductionsupporting
confidence: 83%
“…They concluded that this was a relatively non-specific proteomic response of maize to salt stress, which may indicate disorder of cytoplasmic enzymes due to higher Na + concentration in the cytoplasm. Under identical salt concentrations as those used in this study, the proteome of two wheat genotypes also showed a change of 60% and 79%, respectively (Saqib et al, 2006). Later, proteomic studies on halophytes showed that proteomic alterations under salt stress were specific and less pronounced compared to salt-sensitive plants.…”
Section: Discussionmentioning
confidence: 84%
“…However, the varietal differences, in general, varied with various EC/SAR ratios. Earlier variations among different wheat genotypes for tolerance to salinity have been reported by Davenport et al (2005), Saqib, Zö rb, andSchubert (2006), and Saqib et al (2005). Qureshi, Hanif, and Sandhu (1976) reported a lower green-matter yield of wheat irrigated with unamended saline-sodic tube-well water than with gypsum-amended saline-sodic water.…”
Section: Wheatmentioning
confidence: 81%
“…A few proteins and signaling pathways were found to be commonly regulated among various stress stimuli, including metabolic proteins (carbohydrate, energy, nitrogen metabolism), compatible solutes, and stress-responsive proteins; protein synthesis, protein degradation, and protein turnover as well as reactive oxygen species formation and reactive oxygen species scavenging, including superoxide dismutase, ascorbate peroxidase, and glutathione reductase; and the phenylpropanoid pathway (Kosova et al 2011 ;Suzuki et al 2012 ;Böhmer and Schroeder 2011 ). In wheat, the fi rst response to salt stress is a nonspecifi c response that becomes more specifi c over the course of weeks (Saqib et al 2006 ). Also the initial responses to salt and water stress appear identical, and specifi city develops over a period of time (Munns 2002 ).…”
Section: Changes In Protein Abundance In Response To Abiotic Stressmentioning
confidence: 99%